Adaptive immunity to SARS-CoV-2 infection: A systematic review - Silva, Marcos Jessé Abrahão; Ribeiro, Layana Rufino; Lima, Karla Valéria Batista; Lima, Luana Nepomuceno Gondim Costa (Frontiers in Immunology, 2022)
Background: There is evidence that the adaptive or acquired immune system is one of the crucial variables in differentiating the course of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This work aimed to analyze the immunopathological aspects of adaptive immunity that are involved in the progression of this disease. Methods: This is a systematic review based on articles that included experimental evidence from in vitro assays, cohort studies, reviews, cross-sectional and case-control studies from PubMed, SciELO, MEDLINE, and Lilacs databases in English, Portuguese, or Spanish between January 2020 and July 2022. Results: Fifty-six articles were finalized for this review. CD4+ T cells were the most resolutive in the health-disease process compared with B cells and CD8+ T lymphocytes. The predominant subpopulations of T helper lymphocytes (Th) in critically ill patients are Th1, Th2, Th17 (without their main characteristics) and regulatory T cells (Treg), while in mild cases there is an influx of Th1, Th2, Th17 and follicular T helper cells (Tfh). These cells are responsible for the secretion of cytokines, including interleukin (IL) - 6, IL-4, IL-10, IL-7, IL-22, IL-21, IL-15, IL-1α, IL-23, IL -5, IL-13, IL-2, IL-17, tumor necrosis factor alpha (TNF-α), CXC motivating ligand (CXCL) 8, CXCL9 and tumor growth factor beta (TGF-β), TGF, with the abovementioned first 8 inflammatory mediators related to clinical benefits, while the others to a poor prognosis. Some CD8+ T lymphocyte markers are associated with the severity of the disease, such as human leukocyte antigen (HLA-DR) and programmed cell death protein 1 (PD-1). Among the antibodies produced by SARS-CoV-2, Immunoglobulin (Ig) A stood out due to its potent release associated with a more severe clinical form. Conclusions: It is concluded that through this study it is possible to have a brief overview of the main immunological biomarkers and their function during SARS-CoV-2 infection in particular cell types. In critically ill individuals, adaptive immunity is varied, aberrantly compromised, and late. In particular, the T-cell response is also an essential and necessary component in immunological memory and therefore should be addressed in vaccine formulation strategies.